2006
DOI: 10.1021/la062217y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Hybridization of Oligonucleotides on Mercaptoacetic Acid-Capped CdSe/ZnS Quantum Dots and Quantum Dot−Oligonucleotide Conjugates

Abstract: Interest in the unique optical properties of quantum dots (QDs) has resulted in the development QD-bioconjugates for imaging and diagnostics. Although these applications are numerous, considerably less is known about the interactions between QDs and biomolecules. In this work, we describe hydrogen-bonding interactions between oligonucleotides and CdSe/ZnS quantum dots capped with mercaptoacetic acid ligands. The strength of the interactions can be modulated by changes in the pH and ionic strength, the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 39 publications
3
104
0
Order By: Relevance
“…To reduce the potential steric hinderances, the homopolymer of thymine sequence was employed. Compared with the mixed base sequence or a poly-A sequence, the homopolymer of thymine sequence showed no tendency to adsorb at neutral pH and a greater tendency to adsorb at basic pH (Algar and Krull 2006). Based on these work, TTTTTT was applied to keep the oligonucleotides away from the QDs in this study.…”
Section: Resultsmentioning
confidence: 98%
“…To reduce the potential steric hinderances, the homopolymer of thymine sequence was employed. Compared with the mixed base sequence or a poly-A sequence, the homopolymer of thymine sequence showed no tendency to adsorb at neutral pH and a greater tendency to adsorb at basic pH (Algar and Krull 2006). Based on these work, TTTTTT was applied to keep the oligonucleotides away from the QDs in this study.…”
Section: Resultsmentioning
confidence: 98%
“…We have studied the adsorption of oligonucleotides on MAA-capped QDs using a series of FRET experiments [67]. By fluorescently labeling the oligonucleotide such that the absorption spectrum of the dye overlapped with the PL spectrum of the QD, it was possible to monitor the adsorption of oligonucleotides via FRET-sensitized dye fluorescence.…”
Section: Ligand Exchange and Biomoleculesmentioning
confidence: 99%
“…With respect to conjugated oligonucleotides, it was also possible to investigate the conformation of these oligonucleotides qualitatively via FRET [67]. By varying the acceptor dye position between the 3 0 and 5 0 termini and varying the length of linker between the QD and oligonucleotide, it was determined that the oligonucleotide adopted a conformation along the surface of the QD.…”
Section: Ligand Exchange and Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Adsorptive interactions between oligonucleotides and QDs have also been reported and rationalized in terms of a hydrogen-bonding model. Algar and Krull 10 showed that conjugated oligonucleotides adopt a conformation that lies along the surface of the QD. The formation of these coupled structures is supposed to reduce the donor-acceptor distance and to improve the FRET efficiency.…”
mentioning
confidence: 99%